Direct Amplification of Tissue Factor: Factor VIIa Procoagulant Activity by Bile Acids Drives Intrahepatic Coagulation. Issue 10 (October 2019) - Baker, Kevin S.; Kopec, Anna K.; Pant, Asmita; Poole, Lauren G.; Cline-Fedewa, Holly; Ivkovich, Dora; Olyaee, Mojtaba; Woolbright, Benjamin L.; Miszta, Adam; Jaeschke, Hartmut; Wolberg, Alisa S.; Luyendyk, James P.
Abstract : Objective: Regulation of TF (tissue factor):FVIIa (coagulation factor VIIa) complex procoagulant activity is especially critical in tissues where plasma can contact TF-expressing cells. One example is the liver, where hepatocytes are routinely exposed to plasma because of the fenestrated sinusoidal endothelium. Although liver-associated TF contributes to coagulation, the mechanisms controlling the TF:FVIIa complex activity in this tissue are not known. Approach and Results: Common bile duct ligation in mice triggered rapid hepatocyte TF-dependent intrahepatic coagulation coincident with increased plasma bile acids, which occurred at a time before observable liver damage. Similarly, plasma TAT (thrombin-antithrombin) levels increased in cholestatic patients without concurrent hepatocellular injury. Pathologically relevant concentrations of the bile acid glycochenodeoxycholic acid rapidly increased hepatocyte TF-dependent procoagulant activity in vitro, independent of de novo TF synthesis and necrotic or apoptotic cell death. Glycochenodeoxycholic acid increased hepatocyte TF activity even in the presence of the phosphatidylserine-blocking protein lactadherin. Interestingly, glycochenodeoxycholic acid and taurochenodeoxycholic acid increased the procoagulant activity of the TF:FVIIa complex relipidated in unilamellar phosphatidylcholine vesicles, which was linked to an apparent decrease in the Km for FX (coagulation factor X). Notably, the zwitterionic detergent 3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate, a bile acid structural analog, did not increase relipidated TF:FVIIa activity. Bile acids directly enhanced factor X activation by recombinant soluble TF:FVIIa complex but had no effect on FVIIa alone. Conclusions: The results indicate that bile acids directly accelerate TF:FVIIa–driven coagulation reactions, suggesting a novel mechanism whereby elevation in a physiological mediator can directly increase TF:FVIIa procoagulant activity. Abstract : Supplemental Digital Content is available in the text.